A escolarização e a sua obrigatoriedade: debates na província do Espírito Santo (1870-1880) Schooling and its compulsory nature: debates in the province of Espírito Santo (1870-1880) - Omar Schneider; Amarílio Ferreira Neto; Jeizibel Alves Alvarenga (Educação em Revista, 2012)
A pesquisa busca compreender os debates sobre a escolarização e sua obrigatoriedade na Província do Espírito Santo, entre os anos de 1870 e 1880. Estuda as disputas em relação à implantação de uma forma escolar que se colocava como lugar privilegiado para a formação das futuras gerações, obrigadas a frequentar esse novo espaço de socialização. Os debates indicam que, entre os anos de 1870 e 1880, a escola primária era percebida como o local em que se produziria o homem industrioso, capaz de movimentar a economia e com capacidade inventiva, virtuoso e patriótico para defender a Nação de inimigos internos e externos. Nesse sentido, a confiança no poder da educação também é uma confiança no poder da ciência, no caso, da ciência pedagógica e de seus métodos renovadores da didática de ensino. As disputas permitem perceber representações que faziam parte de um movimento político que reivindicava a obrigatoriedade e a gratuidade do ensino como obrigação do Estado, que busca na escolarização meios para controlar a formação dos professores, com a criação de instituições voltadas para a habilitação para a docência e o investimento em escolas para a infância, com vistas a uma formação modelar do futuro cidadão do Império. This research paper has, as its aim, an understanding of the debates regarding schooling and its compulsoriness in the Province of Espírito Santo, between the years of 1870 and 1880. It examines the disputes that took place with respect to a new school form being implanted, marketed as a place of privilege, with the purpose of preparing the citizens of the future, but with the premise that attending this new "socializing" space, is obligatory. The debates indicate that, between the years 1870 and 1880, primary schools were seen as a place where the industrious man was to be prepared, with a capacity for getting the economy moving and for inventiveness, virtuous and patriotic and therefore ready to defend the Nation against internal and external enemies. In a sense, this faith in the power of education is also a placing of faith in the power of science, on this occasion, pedagogical science, and a faith in its renovating methods of teaching didactics. These disputes allow us to get a taste of the opinions that were part of the political movement that re-invigorated the argument for the State's principle role in establishing an obligatory and state-funded education system, seeking, as it did, ways of organizing teacher formation through the schooling process. Alongside this (achievement) would be the creation of institutions attempting, once more, to bring about the formation of the model citizen of the empire, through education in general, and more specifically, through an investment in Primary schools.